E-cadherin and NM23HI as metastasis predictors for various degrees of histological malignancy in invasive ductal carcinoma (Faculty of Medicine Universitas Indonesia, 2011)
Background: This study aims to analyze whether the expressions of E-cadherin and NM23HI can be used as predictors of ductal carcinoma metastasis in various degrees of malignancies. Methods: Paraffin blocks were obtained from 97 patients with invasive breast ductal carcinoma with malignancy grade 1, 2 and 3 who came to several hospitals in Jakarta and Bandung from 2000 to 2006. Histopathological examinations of hematoxylin eosin slides of primary and secondary tumors were done to diagnose the degree of histological malignancy and metastasis status. Further, immunohistochemistry staining of E-cadherin, NM23HI and cytokeratin were done followed by scoring according to the number of positive cells and staining intensity. The associations of E-cadherin and NM23H1 expression with the presence of metastasis and grade of histological malignancy were analyzed. Results: Subjects were 29-75 years old (mean: 48.19 years), with most subjects aged 40â45 years old, with malignancy grade 1, 2 and 3 of 18.56%, 45.36% and 36.1% respectively. There was a significant association between E-cadherin and NM23HI expression in primary tumors. The possibility of invasion and metastasis inhibition by positive E-cadherin and NM23HI was 14 and 11 times respectively compared to those with negative E-cadherin and/ or NM23HI expression. The ROC curve showed that E-cadherin (r= 0.755) and NM23HI (r= 0.827) expressions were strongly associated, sensitive and specific as metastasis markers. However, E-cadherin and NM23HI expression did not show significant association with histological degree of invasive ductal carcinoma. Conclusion: E-cadherin and NM23HI expressions can be used as invasion and metastasis markers, but cannot be used as markers for the degree of histological malignancy of invasive ductal carcinoma. (Med J Indones 2011; 20:263-70)